Wobec fatalizmu Losu (Stanisław Wyspiański „Klątwa” – John Millington Synge „Jeźdźcy do morza”). Szkic - Olszewska, Maria Jolanta (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The article presents an analysis of two literary works – Klątwa [Curse] by Stanisław Wyspiański (1869–1907) and the Riders to the Sea by John Millington Synge (1871–1909), examined in the context of elements characteristic of ancient tragedy the present in their structure. As a result, although both plays are set in the countryside, they go beyond the naturalistic convention and are more reminiscent of tragic miniatures. They employ the poetics of maximum condensation. Both Klątwa and Riders to the Sea are a modern reading of ancient tragedy, consistently recognised by the authors to be the highest form of playwriting. Wyspiański’s and Synge’s characters are struggling with the real world, with the difficulties of everyday life, but also with the world transcendent to their consciousness, which turns out to be incomprehensible and terrifying at the same time, where forces of Fate rule, to which man is vulnerable. Synge’s heroine surrenders to fate, while the character in Klątwa stands up for herself and fight. Each of them defends her human dignity in her own way.